Estimating the Transmissibility of Mumps: A Modelling Study in Wuhan City, China - Peng, Ying; Yang, Tianlong; Zhu, Yuanzhao; Hu, Qingqing; Wang, Yao; Zhao, Zeyu; Rui, Jia; Lin, Shengnan; Liu, Xingchun; Xu, Jingwen; Yang, Meng; Deng, Bin; et al. (Frontiers in Medicine, 2021)
Despite the adoption of a national immunization program in China, the incidence of mumps remains high. This study aimed to describe the epidemiological characteristics, including time, region, occupation, and age, of mumps in Wuhan from 2005 to 2018 and evaluate its transmissibility. In this study, the Susceptible–Exposed–Infectious–Asymptomatic–Recovered (SEIAR) model fitted the actual incidence data of mumps. The effective reproduction number (Rt) was used to evaluate and compare transmission capacity in different areas. From 2005 to 2018, there were 36,415 cases. The incidence of mumps was highest among people aged 5 to 10 years (460.02 per 100,000). The SEIAR model fitted the reported mumps data well (P < 0.01). The median transmissibility (Rt) was 1.0369 (range: 0 to 2.5016). There were two peak spreads every year (March to May, October to December). The Rt peak always appeared in the first 2 months of the peak incidence rate. The peak time of mumps’ epidemic spread was 1–2 months earlier than the peak incidence rate. Prevention and control measures of vaccination for people aged 5–10 years should be taken before the peak transmission capacity each year, 2 months before the peak of the outbreak, to reduce the spread of mumps.